2013
DOI: 10.4161/onci.25443
|View full text |Cite
|
Sign up to set email alerts
|

B cell-regulated immune responses in tumor models and cancer patients

Abstract: The essential role played by T cells in anticancer immunity is widely accepted. The immunosuppressive functions of regulatory T cells are central for tumor progression and have been endowed with a robust predictive value. Increasing evidence indicates that also B cells have a crucial part in the regulation of T-cell responses against tumors. Although experiments reporting the production of natural antitumor antibodies and the induction of cytotoxic immune responses have revealed a tumor-protective function for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 90 publications
3
96
0
1
Order By: Relevance
“…B cells exogenously pulsed with an antigen can present MHC class II epitopes independently of their B-cell receptor specificity, and also are able to promote MHC class I cross-presentation. 15 Classical (ab) T cells recognize small peptides presented by MHC molecules on the surface of antigen-presenting cells (APCs). Intracellular antigens are subjected to proteolysis, antigenic peptides are bound within the peptide-binding groove of the MHC molecule, and peptide-MHC complexes are transportd to the cell surface for subsequent T cell recognition.…”
Section: Innate and Adaptive Mechanisms For Antitumor Protectionmentioning
confidence: 99%
See 2 more Smart Citations
“…B cells exogenously pulsed with an antigen can present MHC class II epitopes independently of their B-cell receptor specificity, and also are able to promote MHC class I cross-presentation. 15 Classical (ab) T cells recognize small peptides presented by MHC molecules on the surface of antigen-presenting cells (APCs). Intracellular antigens are subjected to proteolysis, antigenic peptides are bound within the peptide-binding groove of the MHC molecule, and peptide-MHC complexes are transportd to the cell surface for subsequent T cell recognition.…”
Section: Innate and Adaptive Mechanisms For Antitumor Protectionmentioning
confidence: 99%
“…IDO expression in DCs is considered to be an important mechanism of immune tolerance. 15 Alternatively activated macrophages (M2s) are generated from circulating monocytes upon IL-4 stimulation. M2s facilitate tumor angiogenesis and promote tumor invasion and metastasis.…”
Section: Immunosuppressive Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Tregs, there is also a subset of B cells described with regulatory capacity, confirmed as regulatory B cells [16,17]. The identification of Bregs in human is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…T cells [18,19]. Further evidences suggested that these Bregs play an essential role in pathogenesis of autoimmune diseases [16]. Although Bregs have been extensively studied in these diseases, there is a little known about their role in human cancer.…”
Section: Introductionmentioning
confidence: 99%